Re-Composing YouTube : Vernacular Musical Aesthetics in the Digital Age - Wolf, Jonas (2024)
YouTube features a wide array of multimodal musical figurations, including fan-made music videos, musical aestheticisations of pre-circulating content, and musical self-performances. Jonas Wolf explores open-ended forms of musical creative relay on YouTube, delving into formal, imitative, affective, and (non-)institutional aspects of networked media remix and (self-)aestheticisation. Beyond creating value for non-musical fields of discourse, this study is directed at filling a gap in a largely ocularcentric domain of study. It provides a concise theory of vernacular composition within our time's total digital archive that accounts for socio-aesthetic phenomena and their relation to systems of knowledge, control, and discourse.